2018
DOI: 10.1093/schbul/sby087
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic Experiences and Related Distress: A Cross-national Comparison and Network Analysis Based on 7141 Participants From 13 Countries

Abstract: Psychotic experiences (PEs) are common in the general population but do not necessarily reflect a risk status if they occur in relative isolation or are not distressing. Emerging evidence suggests that PEs might be experienced as more benign for individuals from collectivistic low- and middle-income countries (LAMIC) compared with individualistic high-income countries (HIC). The aim of this study was to determine whether: (1) self-reported PEs are less distressing in community samples from LAMIC than from HIC;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
58
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 69 publications
7
58
1
1
Order By: Relevance
“…To improve our understanding of the dynamics between co-occurring autistic traits, psychotic traits, and functioning in PD, it would therefore be of great interest to study the strength of relations on a subdomain level and determine centrality measures within a network approach (van Rooijen et al, 2018;Wigman et al, 2015;Wüsten et al, 2018). Social cognitive functioning was also negatively associated with autistic traits in line with previous findings Vaskinn & Abu-Akel, 2019) but, contrary to expectations, the effect was small and comparable across groups.…”
Section: Discussionsupporting
confidence: 72%
“…To improve our understanding of the dynamics between co-occurring autistic traits, psychotic traits, and functioning in PD, it would therefore be of great interest to study the strength of relations on a subdomain level and determine centrality measures within a network approach (van Rooijen et al, 2018;Wigman et al, 2015;Wüsten et al, 2018). Social cognitive functioning was also negatively associated with autistic traits in line with previous findings Vaskinn & Abu-Akel, 2019) but, contrary to expectations, the effect was small and comparable across groups.…”
Section: Discussionsupporting
confidence: 72%
“…Similar findings have been reported with regard to the prevalence of positive symptom clusters across different ethnic groups within certain countries: disparity in symptom prevalence between ethnic groups exceeds disparity in prevalence of psychotic disorder [3739]. This seems to be especially true for perceptual anomalies and paranoia [4042]. Moreover, discrepancies between positive symptom prevalence and prevalence of a diagnosis of psychosis have been shown to be more pronounced in some ethnic groups than in others [10, 37, 39, 43], pointing towards a complex interplay of cultural and social factors (e.g.…”
Section: Introductionsupporting
confidence: 75%
“…Although this meta-analysis [25] included samples from different parts of the world, the focus was mainly on identifying general underlying symptom structures, rather than comparing symptom prevalence across cultural groups or study samples. Moreover, the reviewed samples were from the so-called Western World, and to date CAPE-42 psychotic experiences have been rarely investigated in African study samples [22, 42].…”
Section: Introductionmentioning
confidence: 99%
“…These results are also congruent with previous studies. Network models have also been used to analyze, amongst others, schizotypal personality traits in a multinational sample (54), psychotic like-experiences in crosscultural study (64), and psychotic-like experiences in a large U.S. sample (65). For instance, Fonseca-Pedrero et al, (54), using the Schizotypal Personality Questionnaire (66), indicated that schizotypal traits were strongly interconnected in the domainlevel network.…”
Section: Discussionmentioning
confidence: 99%